Association of Physical Activity Measured by Accelerometer, Knee Joint Abnormalities, and Cartilage T2 Measurements Obtained From 3T Magnetic Resonance Imaging: Data From the Osteoarthritis Initiative. Issue 9 (26th August 2015) - Kretzschmar, M.; Lin, W.; Nardo, L.; Joseph, G. B.; Dunlop, D. D.; Heilmeier, U.; Nevitt, M. C.; Alizai, H.; McCulloch, C. E.; Lynch, J. A.; Link, T. M.
Abstract : Objective: To study the cross‐sectional association between physical activity measured with an accelerometer, structural knee abnormalities, and cartilage T2 values assessed with 3T magnetic resonance imaging (MRI). Methods: We included 274 subjects from the Osteoarthritis Initiative cohort without definite radiographic osteoarthritis (Kellgren/Lawrence grades 0 and 1) and with at most mild pain, stiffness, and functional limitation in the study knee (Western Ontario and McMaster Universities Osteoarthritis Index scale 0–1), which had not limited their activity due to knee pain. Physical activity was measured over 7 days with an ActiGraph GT1M accelerometer. Subjects were categorized by quartile of physical activity based on the average daily minutes of moderate to vigorous physical activity (mv‐PA). MRI images of the right knee (at 48‐month visit) were assessed for structural abnormalities using a modified Whole‐Organ Magnetic Resonance Imaging Score (WORMS) and for T2 relaxation times derived from segmented cartilage of 4 femorotibial regions and the patella. WORMS grades and T2 measurements were compared between activity quartiles using a linear regression model. Covariates included age, sex, body mass index, knee injury, family history of knee replacement, knee symptoms, hip and ankle pain, and daily wear time of the accelerometer. Results: Higher mv‐PA was associated with increased severity ( P  = 0.0087) and number of lesions of the medial meniscus ( P  = 0.0089) and with severity of bone marrow edema lesions ( P  = 0.0053). No association between cartilage lesions and mv‐PA was found. T2 values of cartilage (loss, damage, and abnormalities) tended to be greater in the higher quartiles of mv‐PA, but the differences were nonsignificant. Conclusion: In knees without radiographic osteoarthritis in subjects with no or mild knee pain, higher physical activity levels were associated with increases in meniscal and bone marrow edema pattern lesions.